Diversity analysis of Rhacophorus margaritifer (Schlegel, 1837) in Baturraden based on RAPD markers - Fajar Nur Sulistyahadi; I Gusti Agung Ayu Ratna Puspitasari; Agus Nuryanto (Universitas Gadjah Mada, 2020)
Rhacophorus margaritifer is an endemic species of arboreal frog in Java. Previous studies found this frog in several locations of Baturraden, namely in primary forest of Ketenger area, along Pancuran Pitu tourism track, and Baturraden Botanical Garden. There were still limited studies of molecular diversity of R. margaritifer and no prior data from population in the southern slope of Mount Slamet. This study aimed to look at the genetic polymorphism and determine the locus diversity of R.margaritifer population in Baturraden by using the PCR-RAPD technique. Frog tissue samples were taken from three populations in Kalipagu hiking trail (HPK 01), Baturraden hiking trail (HPK 02), and Baturraden Botanical Garden (KRB). DNA was extracted using the Chelex method. Molecular characterization was performed based on RAPD markers. The RAPD marker band pattern was changed to binary data 0-1 and analysed using Arlequin software ver.3.5. A total of 19 frog individuals were obtained during sampling at three locations. High genetic diversity had been observed in all populations with gene diversity range from 0.9643 in HPK 01 population to 1.0000 in both KRB and HPK 02 populations. A high locus variation was also observed for all populations with values of 0.159524 in KRB; 0.165816 in HPK 01; 0.192857 in HPK 02, respectively. AMOVA indicated no genetic difference among populations of R. margaritifer (p=0.50244).